Pengaruh Model Make A Match Terhadap Minat Belajar Peserta Didik Pada Muatan Materi PPKn Kelas IV SDN 26 Cakranegara Tahun Pelajaran 2021/2022 - Hadijah, Siti; Nisa, Khairun; Jiwandono, Ilham Syahrul (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
This study aims to determine the effect of the Make A Match learning model on students' learning interest in the fourth grade content of SDN 26 Cakranegara. This type of research is a quasi-experimental type of nonequivalent control group design. The sampling technique used is census or total sampling. The total number of samples is 82 students. The data collection method used was in the form of observation and student learning interest questionnaires, questionnaires were used for student learning interest data that had previously been tested for validity and reliability in the form of pretest and posttest. Then analyzed using normality test, homogeneity test, hypothesis test and further test with effect size test. Based on the interest in learning data analyzed using the t-test (t-test) obtained tcount of 2,957 while ttable of 1,990 at a confidence level of 5% (0.05), so it can be concluded that (Ha) is accepted and (H0) is rejected. The follow-up test in this study used the Cohen's d effect size formula with the results of 0.781 > 0.6 which means that the effect of the make a match learning model on learning interest is included in the large category based on the effect size classification.